Green and brown propolis: efficient natural biocides for the control of bacterial contamination of alcoholic fermentation of distilled beverage - Mutton, Márcia Justino Rossini [UNESP]; Oliveira Filho, José Humberto de [UNESP]; Costa, Gustavo Henrique Gravatim [UNESP]; Roviero, Juliana Pelegrini [UNESP]; Freita, Lidyane Aline de [UNESP] (Sociedade Brasileira de Ciência e Tecnologia de Alimentos, 2014)
This study aimed to evaluate the efficiency of natural biocides, brown and green propolis, for the control of bacterial contamination in the production of sugarcane spirit. The treatments consisted of brown and green propolis extracts, ampicillin, and a control and were assessed at the beginning and end of harvest season in ten fermentation cycles. In the microbiological analyses, the lactic acid bacteria were quantified in the inoculum before and after the treatment with biocides, and the viability of yeast cells during fermentation was evaluated. The levels of acids, glycerol, total residual reducing sugars, and ethanol were analyzed for the wine resulting from each fermentation cycle. A reduction in the number of bacterial contaminants in the inoculum in the treatments with the natural biocides was observed, but it did not affect the viability of yeast cells. The control of the contaminants led to the production of higher levels of ethanol and reduced acidity in the wine produced. The results of the use of brown and green propolis to control the growth microorganisms in the fermentation of sugarcane spirit can be of great importance for using alternative strategies to synthetic antibacterials in fermentation processes including other distilled beverage or spirits.
Keywords: Sugarcane spirit; Antimicrobials; Natural products; Lactic acid bacteria; Ethanol